2021
DOI: 10.3390/ijerph18179257
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of a Contact Tracing Training Program for COVID-19 in Greece Focusing on Vulnerable Populations

Abstract: Background: Contact tracing as an epidemiological strategy has repeatedly contributed to the containment of various past epidemics and succeeded in controlling the spread of disease in the community. Systematic training of contact tracers is crucial in ensuring the effectiveness of epidemic containment. Methods: An intensive training course was offered to 216 health and other professionals who work with vulnerable population groups, such as Roma, refugees, and migrants in Greece, by the scientific team of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A German study [ 10 ] found that a higher level of education led to improved adoption of pandemic apps. In Belgium, a survey found a large majority of nonusers This refusal of use was largely due to privacy concerns and ambivalence about the app’s utility [ 11 ]. In Greece, an in-depth additional contact-tracing training study found that contact-tracing efforts work best in a systematic and coordinated manner, and systematic and organized training of contact-tracing workers can greatly increase its effectiveness [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A German study [ 10 ] found that a higher level of education led to improved adoption of pandemic apps. In Belgium, a survey found a large majority of nonusers This refusal of use was largely due to privacy concerns and ambivalence about the app’s utility [ 11 ]. In Greece, an in-depth additional contact-tracing training study found that contact-tracing efforts work best in a systematic and coordinated manner, and systematic and organized training of contact-tracing workers can greatly increase its effectiveness [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Participants suggested that a greater emphasis be placed on practical on-site training with longer periods of shadowing and one to one supervision as this was perceived to better prepare them for the role. The provision of online discussion sessions and online role playing exercises [29], which can improve health communication skills and cultural competencies [33], may also help in building contact tracers' skills and confidence in emotionally charged situations [10,34].…”
Section: The Contact Tracing Rolementioning
confidence: 99%
“…The digital contact-tracing system could play a major role in secondary prevention, where exposed individuals could receive a notification so that they could comply with the regulations at the material time for, inter alia, undergoing testing and quarantine [ 10 ]. By identifying, isolating, and treating infected individuals, the transmission risk in the population could be minimised (primary prevention) [ 11 ], and the risk and severity of disease development could be reduced by early treatment (tertiary prevention). Thus, a digital contact-tracing system could become a gateway to all three levels of prevention.…”
Section: Introductionmentioning
confidence: 99%